Analisis Pengaruh Kompetensi Dosen, Disiplin Kerja Dosen, Dan Dukungan Organisasi Terhadap Pengembangan Profesi Dosen Tetap (Studi Kasus : Fakultas Ekonomi Universitas Pamulang) - Fitri Konefi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aimed to analyze the effect lecturer’s competence, lecturer’s work discipline and organization’s support toward lecturer’s professional development in the faculty of economics Pamulang University. This research approach using quantitative research methods with observation method structured interviews and questionnaires closed. The population in this research is a lecturer Pamulang University economics faculty, while the sampling technique used is proporsionale stratified random sampling. The results indicate that there is positive and significant correlation between lecturer’s competence toward lecturer’s professional development, there is positive and significant correlation between lecturer’s work discipline toward lecturer’s professional development, there is positive and significant correlation between organization’s support toward lecturer’s professional development, and there is positive and significant correlation between the lecturers competence, lecturer’s work discipline and organization’s support together toward lecturer’s professional development. So can be concluded that there is a significant positive effect between of lecturer’s competence, of lecturer’s work discipline and organization’s support toward lecturer’s professional development in the faculty of economics Pamulang University.